2021
DOI: 10.1016/j.xfnr.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the gut microbiome in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a widespread endocrine disorder that affects women of reproductive age. Recent studies have demonstrated a close association between the gut microbiome and PCOS. Their microbial diversity may not significantly change, and the crucial role of Bacteroides spp. has been demonstrated in human PCOS. Furthermore, animal models of PCOS exhibit gut microbiome features different from those of humans with PCOS. The gut microbiome may differ in patients with PCOS because it can be affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…This change can be attributed to the bubble template process, which introduces disorder and porosity into the material structure, thereby disrupting the π‐conjugated system. [ 39 ] On the other hand, the decreased bandgap observed in CN‐NaK and CN‐NH 4 ‐NaK can be attributed to the extension of the π‐conjugated system, indirectly indicating a decrease in the number of terminal amino groups. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This change can be attributed to the bubble template process, which introduces disorder and porosity into the material structure, thereby disrupting the π‐conjugated system. [ 39 ] On the other hand, the decreased bandgap observed in CN‐NaK and CN‐NH 4 ‐NaK can be attributed to the extension of the π‐conjugated system, indirectly indicating a decrease in the number of terminal amino groups. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…This change can be attributed to the bubble template process, which introduces disorder and porosity into the material structure, thereby disrupting the 𝜋-conjugated system. [39] On the other hand, the decreased bandgap observed in CN-NaK and CN-NH 4 -NaK can be attributed to the extension of the 𝜋-conjugated system, indirectly indicating a decrease in the number of terminal amino groups. [38] VB-XPS spectra was used to estimate the valence band (E VB, XPS ) of the prepared samples, as detailed in Figure S3 It is reported that the flat band potential of an n-type semiconductor equals its conduction band potential (E CB ).…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
“…anchored Fe 2 dimers on several carbon nanosheets to highlight the significance of electronic metal‐support interaction on the NRR performance with the assist of spin‐polarized DFT. [ 212 ] To be specific, these 2D carbon supports include defective graphene with pristine (C‐DV/G) or porphyrin‐like divacancy (N‐DV/G), graphdyine (GDY), and graphic carbide nitride (g‐C 3 N 4 ). The analyses indicate that the Fe 2 dimer can be firmly attached at the defect sites of these carbon substrates, resulting in the polarized positive charges accumulation at the Fe dimer center, accelerating the adsorption and activation process of the inert N 2 molecule.…”
Section: Regulation Of the Active Moiety Of Dual‐atom Site Electrocat...mentioning
confidence: 99%
“…5 With the rapid development of sequencing technology, changes in gut microbes have been confirmed in PCOS patients and in animal models of PCOS. 6 In addition, the manipulation of gut microbes, such as by faecal microbiota transplantation and cohousing of mice, affects PCOS phenotypes. 7,8 These findings indicate that treatments targeting the gut microbiota may be promising therapeutic strategies for PCOS.…”
Section: Introductionmentioning
confidence: 99%